A Spectroscopic Investigation of Eu3+ Incorporation in LnPO4 (Ln = Tb, Gd1-xLux, X = 0.3, 0.5, 0.7, 1) Ceramics - Lösch, Henry; Hirsch, Antje; Holthausen, Jacqueline; Peters, Lars; Xiao, Bin; Neumeier, Stefan; Schmidt, Moritz; Huittinen, Nina (Frontiers in Chemistry, 2019)
We have investigated the incorporation of the luminescent Eu3+ cation in different LnPO4 (Ln = Tb, Gd1–xLux, x = 0.3, 0.5, 0.7, 1) host phases. All samples were analyzed with powder X−ray diffraction (PXRD), Raman spectroscopy, and site selective time–resolved laser–induced luminescence spectroscopy (TRLFS) directly after synthesis and after an aging time of one year at ambient conditions. The PXRD investigations demonstrate the formation of a TbPO4 phase in an uncommon anhydrite–like crystal structure evoked by a pressure–induced preparation step (grinding). In the Gd1–xLuxPO4 solid solution series, several different crystal structures are observed depending on the composition. The TRLFS emission spectra of LuPO4, Gd0.3Lu0.7PO4, and Gd0.5Lu0.5PO4 indicate Eu3+–incorporation within a xenotime–type crystal structure. TRLFS and PXRD investigations of the Gd0.7Lu0.3PO4 composition show the presence of anhydrite, xenotime, and monazite phases, implying that xenotime no longer is the favored crystal structure due to the predominance of the substantially larger Gd3+–cation in this solid phase. Eu3+–incorporation occurs predominantly in the anhydrite–like structure with smaller contributions of Eu3+ incorporated in monazite and xenotime. The electronic levels of the Eu3+–dopant in Gd0.3Lu0.7PO4 and Gd0.5Lu0.5PO4 xenotime hosts are strongly coupled to external lattice vibrations, giving rise to high–energy peaks in the obtained excitation spectra. The coupling becomes stronger after aging to such an extent that direct excitation of Eu3+ in the xenotime structure is strongly suppressed. This phenomenon, however, is only visible for materials where Eu3+ was predominantly incorporated within the xenotime structure. Single crystals of Eu3+–doped LuPO4 show no changes upon aging despite the presence of vibronically coupled excitation peaks in the excitation spectra measured directly after synthesis. Based on this observation, we propose a lattice relaxation process occurring in the powder samples during aging, resulting in Eu3+ migration within the crystal structure and Eu3+ accumulation at grain boundaries or xenotime surface sites.